Enteroparasitary contamination of the tabure river, Palavecino Municipality, Lara State, Venezuela (Salud, Arte y Cuidado, 2017)
To study the possibility of enteroparasitic contamination of the Quebrada Tabure (Tabure River), a product of untreated wastewater discharge, a descriptive cross sectional study was carried out, where 112 water samples were analyzed at different heights along the Quebrada, which crosses the Cabudare city, Palavecino municipality of Lara state, Venezuela. The samples were collected with a clean injector of 20 ml, attached to a clear and clean hose, 60 ml of water were collected per sample, to be studied later, being able to appreciate a low diversity, but a high abundance of enteroparasites, being detected: Blastocystis sp (9.83% of the analyzed samples), Chilomastix mesnili (8,19%), Entamoeba histolytica / Entamoeba dispar (6,55%), Ascaris lumbricoides (4,91%), Endolimax nana (3,27%) and starting from the chemical pollution of these waters can destroy many protozoa and helminths, the abundance and diversity of species is below the real values. These results are in agreement with prevalences of enteroparasites of patients of Cabudare, where Blastocystis sp, is the most frequent, oscillating between 20 and 40%, reason why it is the most frequent contaminating the waters of this Quebrada. According to the WHO, the presence of ≥1 Ascaris lumbricoides egg per liter of water, disables water for irrigation or agricultural use, and therefore cannot be reused, therefore, these waters are an epicenter of parasitic contamination for the population of Cabudare
Keywords: blastocystis; parasites; water; river